The revolutionary role of placental derivatives in biomedical research - Saeid Moghassemi; Saba Nikanfar; Arezoo Dadashzadeh; Maria João Sousa; Yuting Wan; Fengxuan Sun; Arthur Colson; Sven De Windt; Lena Kwaspen; Marc Kanbar; Keyvan Sobhani; Jie Yang; et al. (Bioactive Materials)
The human placenta is a transient yet crucial organ that plays a key role in sustaining the relationship between the maternal and fetal organisms. Despite its historical classification as “biowaste,'' placental tissues have garnered increasing attention since the early 1900s for their significant medical potential, particularly in wound repair and surgical application. As ethical considerations regarding human placental derivatives have largely been assuaged in many countries, they have gained significant attention due to their versatile applications in various biomedical fields, such as biomedical engineering, regenerative medicine, and pharmacology. Moreover, there is a substantial trend toward various animal product substitutions in laboratory research with human placental derivatives, reflecting a broader commitment to advancing ethical and sustainable research methodologies. This review provides a comprehensive examination of the current applications of human placental derivatives, explores the mechanisms behind their therapeutic effects, and outlines the future potential and directions of this rapidly advancing field.